2008
DOI: 10.1590/s0044-59672008000400005
|View full text |Cite
|
Sign up to set email alerts
|

Composição e diversidade florístico-estrutural de um hectare de floresta densa de terra firme na Amazônia Central, Amazonas, Brasil

Abstract: Composition and floristic-structural diversity of a hectare of terra firme dense forest in Central Amazonia, Amazonas, Brazil aBSTRacT to investigate the composition and floristic diversity of one hectare of a dense forest on a terra firme oxisol plateau, 90 km from the manaus (02º35'45" s e 60º12'40" W), all trees, lianas and palm trees with diameter at breast height (DBh) ≥ 10 cm were inventoried along two parallel transects of 500 x 10 m. the landscape is vegetationally exuberant and homogeneous, with a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
1
46

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 28 publications
7
36
1
46
Order By: Relevance
“…Similar to Boubli (2002), we found that 40% of the trees registered in white-sand and terra-firme plots have a DBH between 10 and 15 cm. Comparable diameter size-class distributions have been commonly reported for terra-firme forests in other regions of Amazonia (Amaral et al 2000;Lima Filho et al 2001;Pitman et al 2002;Oliveira and Amaral 2004;Oliveira et al 2008).…”
Section: Forest Structurementioning
confidence: 49%
“…Similar to Boubli (2002), we found that 40% of the trees registered in white-sand and terra-firme plots have a DBH between 10 and 15 cm. Comparable diameter size-class distributions have been commonly reported for terra-firme forests in other regions of Amazonia (Amaral et al 2000;Lima Filho et al 2001;Pitman et al 2002;Oliveira and Amaral 2004;Oliveira et al 2008).…”
Section: Forest Structurementioning
confidence: 49%
“…The representativeness of these families as hosts is understandable, since these are the most diverse and abundant families according to various floristic surveys in the Amazon, although these studies do not associate them with the epiphytic community (Amaral et al 2000;Duque et al 2003;Oliveira et al 2008;Silva et al 2008). This result may indicate that epiphytes occurred more frequently on these phorophytes because these species possess a wide distribution, as well as high density in terra firme forests in the Amazon and, therefore, the majority of available species and individuals in this forest may be conducive to epiphytic colonization.…”
Section: Resultsmentioning
confidence: 99%
“…The lower DBH classes concentrate 70% of the total volume per hectare ( Figure 6). Trees of the Eschweilera genus with a DBH ≥ 50 cm are rare and sparse [25,26,28,39,40]. Paragraph 3 of the CONAMA resolution allows for changes to the minimum diameter permitted for logging (DMC) [38].…”
Section: Discussionmentioning
confidence: 99%
“…However, these differences are not well distributed in terms of number of individuals (abundance) [16]. There are only a few botanical genera that represent nearly half of all trees in the Amazon, with the Eschweilera, Protium, and Euterpe genera being the most abundant [16,40,42]. Trees of the Eschweilera genus, aside from their huge abundance in the Amazon basin [16], have a large density of individuals in the central Amazon [28].…”
Section: Discussionmentioning
confidence: 99%